IDENTIFICATION AND MORPHOLOGICAL CHARACTERIZATION OF PERONOSCLEROSPORA MAYDIS CAUSING DOWNY MILDEW ON MAIZE IN LANGKAT AND SIMALUNGUN REGENCIES - Rohayati Sitanggang; Syamsafitri; Noverina Chaniago (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Downy mildew, caused by oomycetes of the genus Peronosclerospora, is the most destructive biotic threat to maize cultivation in Indonesia, with the potential to cause up to 100% yield loss. Accurate species identification is crucial for determining effective control strategies. This study aimed to identify and characterize the Peronosclerospora spp. responsible for downy mildew in eight survey locations across Langkat and Simalungun Regencies, North Sumatra. The research involved field surveys and laboratory microscopic observations to analyze qualitative (morphological) and quantitative (morphometric) parameters. Identification results indicated that all pathogen isolates from the eight locations were Peronosclerospora maydis. Morphologically, the pathogen featured hyaline conidiophores that were clustered, with 2–4 dichotomous branches. Morphometrically, structural variations were observed, with conidiophore lengths ranging from 150–550 µm and conidial diameters between 17–23 x 27–39 µm. Conidia were predominantly spherical to subspherical with thin cell walls. These dimensional variations are suggested to be influenced by external factors such as local agroclimatic conditions and host genotypes. This study confirms that P. maydis remains the primary pathogen causing downy mildew in North Sumatra.